Identification of DIR1-Dependant Cellular Responses in Guard Cell Systemic Acquired Resistance - David, Lisa; Kang, Jianing; Nicklay, Josh; Dufresne, Craig; Chen, Sixue (Frontiers in Molecular Biosciences, 2021)
After localized invasion by bacterial pathogens, systemic acquired resistance (SAR) is induced in uninfected plant tissues, resulting in enhanced defense against a broad range of pathogens. Although SAR requires mobilization of signaling molecules via the plant vasculature, the specific molecular mechanisms remain elusive. The lipid transfer protein defective in induced resistance 1 (DIR1) was identified in Arabidopsis thaliana by screening for mutants that were defective in SAR. Here, we demonstrate that stomatal response to pathogens is altered in systemic leaves by SAR, and this guard cell SAR defense requires DIR1. Using a multi-omics approach, we have determined potential SAR signaling mechanisms specific for guard cells in systemic leaves by profiling metabolite, lipid, and protein differences between guard cells in the wild type and dir1-1 mutant during SAR. We identified two long-chain 18 C and 22 C fatty acids and two 16 C wax esters as putative SAR-related molecules dependent on DIR1. Proteins and metabolites related to amino acid biosynthesis and response to stimulus were also changed in guard cells of dir1-1 compared to the wild type. Identification of guard cell-specific SAR-related molecules may lead to new avenues of genetic modification/molecular breeding for disease-resistant plants.